Zakat dan Perannya dalam Memajukan Keadilan dan Kesetaraan Sosial - Marzuki Marzuki; Resfika Elsa Nadila (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Those who practice Islam are obliged to pay zakat, which is a kind of zakat that must be distributed according to Islamic law,to thosewhoareable toreceive it.One of the pillars of Islam that is used to improve social welfare and welfare is zakat. Zakat is a means that Muslims hope to alleviate material and spiritual poverty, foster social solidarity, and provide for the general public.Various sources indicate that zakat is not only a religious obligation but also an effective instrument in providing food and alleviating social suffering.